Implementasi Metode Demonstrasi dalam Pembelajaran Mufradat Bahasa Arab di MIS Tanwirul Islam II Sampang - Hasyim Asy’ari, Moh. (AL -ALLAM, 2026)
In Arabic, vocabulary is one of the elements of Arabic, vocabulary is a very important element of Arabic so that students can understand the next Arabic language materials, and in learning vocabulary, appropriate methods are also needed, among the methods that are appropriate for vocabulary learning is the demonstration method. In understanding vocabulary, students at MIS Tanwirul Islam II are very lacking, because when teachers teach using less effective methods and students become bored. This research approach uses a qualitative approach with a case study type, in data collection, researchers use observation, interviews, documentation and data analysis. The results of this study are that the implementation of the demonstration method in learning Arabic vocabulary at MIS Tanwirul Islam II is very effective with students being more enthusiastic and more enthusiastic in participating in vocabulary learning. And the supporting factors that influence students in implementing the demonstration method include high student interest and the existence of effective learning media such as image media and others, and inhibiting factors, namely the lack of teacher understanding of the material.